Employment of Body Language in Television Advertising An Analytical Study of Al-Hayat TV Commercials (The Egyptian Series as a Model) - Shibeeb, Huda Malik; Abdul Hadi, Zina (ALBAHITH ALALAMI, 2013)
Whatever the designers of the advertisement in choosing the text and spoken phrases, those phrases cannot give or convey the full meaning to the recipient only if this spoken and written language is reinforced with another language based on the signals, movements, and symbols that are displayed using the body or other artistic elements of the advertisement such as pictures, colors, music, effects, and other elements used in the artistic construction of television advertising. All these artistic elements contribute to the completion of the advertising idea and make it ready to be displayed to the public. Scientists and researchers, in the field of psychology, have relied a lot on this language (body language). And some of them put many interpretations and variety of every movement and every signal made by human beings. Non-verbal language has become very important to know the personality of the human, and how to think. Moreover, this kind of language expresses deeply hidden feelings. The number of these movements, which those scientists and researchers interpreted, have reached to (130) movements carried out by man without uttering a word to what he wants to say. Advertisers and designers did not hesitate to rely on this language in presenting their advertising idea. Some of the ads, though, are sometimes devoid of verbal language and only refer to the language of silence. Yet, they proved their success in delivering what they want to deliver to the public. From this point of view, the researchers in this field decided to find out the extent of using this language in television advertisements based on the survey method, which is the appropriate method to describe the phenomenon (the subject of the research). They, in addition, used the content analysis method. The two researchers designed an analysis form that included sub-categories of all comprehensive movements of the body, head, limbs, and the body in general. The two researchers have reached important results, the most important of which are: • Al-Hayat TV series focused on the use of body language in its advertisements, believing in the impact of this language on the recipient to reach the speed of response. • The head category was the highest rate used in most ads of the channel because it includes other parts face, eyebrows, nose, ear, and mouth. All these perform a specific language that supports the verbal language. • Beverage ads get the highest percentage in the use of body language. • The superiority of the physical language over the verbal language in the ads of the channel during the recording period of the sample.